2023
DOI: 10.7759/cureus.36653
|View full text |Cite
|
Sign up to set email alerts
|

Mean SOFA Score in Comparison With APACHE II Score in Predicting Mortality in Surgical Patients With Sepsis

Abstract: Background: Sepsis is a medical and surgical emergency that describes the body's systemic immunological response to an infectious process that can lead to end-stage organ dysfunction and death. Various clinical and biochemical parameters serve as indicators of organ dysfunction in patients with sepsis. Most familiar among them are the Sequential Organ Failure Assessment (SOFA) score, Acute Physiology and Chronic Health Evaluation (APACHE) II score, Mortality Prediction Score (MPM), and Simplified Acute Physiol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
0
1
0
Order By: Relevance
“…Midkine levels were measured using an ELISA kit (Catalog#: CSB-E08892h, Wuhan Epitope Biotechnology Co., Ltd.), the intra-assay coefficient of variation is 5.84%, the inter-assay coefficient of variation is 5.41%, and the detection range is 0.1 to 100 ng/mL;Omentin-1 levels were measured using an ELISA kit (Catalog#: XY2457A, Shanghai XuanYa Biotechnology Co., Ltd.), The intra-assay coefficient of variation is 5.91%, the inter-assay coefficient of variation is 5.77%, and the detection range is 10 to 1000 ng/mL. The severity of sepsis patients within 24 hours of admission was assessed using the APACHE II scoring system [ 10 ].…”
Section: Methodsmentioning
confidence: 99%
“…Midkine levels were measured using an ELISA kit (Catalog#: CSB-E08892h, Wuhan Epitope Biotechnology Co., Ltd.), the intra-assay coefficient of variation is 5.84%, the inter-assay coefficient of variation is 5.41%, and the detection range is 0.1 to 100 ng/mL;Omentin-1 levels were measured using an ELISA kit (Catalog#: XY2457A, Shanghai XuanYa Biotechnology Co., Ltd.), The intra-assay coefficient of variation is 5.91%, the inter-assay coefficient of variation is 5.77%, and the detection range is 10 to 1000 ng/mL. The severity of sepsis patients within 24 hours of admission was assessed using the APACHE II scoring system [ 10 ].…”
Section: Methodsmentioning
confidence: 99%
“…Currently, sequential organ failure assessment (SOFA) component scores are used in clinical risk stratification of patients with sepsis; however, they have limitations of poor specificity and sensitivity. 7 8 9 10 11 The SOFA score is one of the main criteria for sepsis-3 definitions. Several previous studies have suggested predictive results for patients with sepsis using the SOFA score; however, they have achieved varying performances in predicting short-term mortality.…”
Section: Introductionmentioning
confidence: 99%